As estratégias de reprodução de sitiantes no Oeste de Minas Gerais e de colonos no Sudoeste do Paraná - Perondi, Miguel Ângelo (1999)
This study aims to analyze the reproductive strategies offamily farmers, through similar evidences found in two rural communities. The productive and reproductive processes are simultaneous, andthe contínuos reuse of a part ofthe product to obtain new means of production, recreate the social and cultural conditions for the existence ofthe farmers. The reproductive effort is revealed whenone observeshow the tamily work is organized, how they do the succession, howthey increase the patrimony, and howthey conquest new agriciütural and no agricultural activrtíes for improving their financial situation. In this work we begin presenting the theory and methodology used to analyze the study subject. Afterwards two rural communities are described: one in Minas Gerais' Western part and other in Paraná's Southwestern. Finally, the reproductive strategies appearing in both cases are analyzed. It was noticed that the familylabor division is dynamically, but fíxed by the economic relevance ofthe activity, according the criteria money/men and support/woman. Similar to the way they prepare their successorand how they use the land acquisrtíon to adjust ofthe inheritance. The savings are represented by the cattle for the "sitiantes" and the historical equivalent are the pigs for the "colonos". The migration and pluriactivity appear as fundamental instruments for increasing the patrimony ofyoung adults. In both casesthere appeared the figure of the rural businessman played by a member of the community. Therefore, the reproductive strategies showed to be similarfor the development of the family exploitation unit, when conflict and alliances, internal and extemal pressures, act on itself, in an effort of self exploitation and self reproduction.